ORAL OPIOID ANALGESICS VS SPINAL STEROID INJECTIONS IN THE TREATMENT OF LOW BACK PAIN: A COMPREHENSIVE SYSTEMATIC REVIEW - Agus Prastyo, Wahyu; Nugraheni, Artha Investari; Azhari, Ririn; Merisa L, Bella; Yulanda Putra, Yosie; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Low back pain (LBP) affects a significant portion of the population worldwide, with distinct treatment needs for acute and chronic cases. Despite widespread opioid use, evidence for their efficacy in LBP remains uncertain, highlighting the need for alternative interventions. Minimally invasive procedures like epidural steroid injections offer potential relief for conditions like lumbar disc herniation, but their effectiveness is debated. To address these complexities, we conducted a comprehensive review encompassing various treatment modalities beyond medication, aiming to optimize outcomes and improve quality of life for individuals with LBP. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 13 results. After looking at the titles and summaries, we found 8 papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included four papers in our final analysis. These papers included retrospective analysis, a randomized, double blind, placebo controlled cross-over study, noninterventional, retrospective 12-week study using anonymized clinical practice data from the German Pain eRegistry, and a retrospective analysis of anonymized, propensity score–matched data. Conclusion: Favorable post-injection outcomes suggest the blind method for caudal epidural injections is safe and effective, suitable for patients not eligible for surgery or unresponsive to conservative treatments. Interlaminar epidural steroid injections effectively reduce VAS and ODI scores in patients with chronic low back pain and multi-level disc disease, but further research is needed to standardize administration protocols and optimize treatment outcomes, including addressing BMI's impact. The analgesic efficacy of periradicular meloxicam injections for acute/subacute low back pain, indicating a potential new treatment option, while real-world data suggest NBX oromucosal spray may be superior to typical oral LAO analgesics for severe peripheral NBP, pending confirmation in large RCTs.